Factors Influencing the Perception of Corruption in the Countries of the European Union - Botond Géza Kálmán; Endre Béla Huff; Anh Tuan Hoang; Viharos Zsolt János; Zoltán Zéman (Emerging Science Journal)
Objectives: The European Union regularly publishes reports on corruption as part of its Eurobarometer surveys. These report on the opinions of European citizens regarding corruption and the presence of corruption they perceive. Based on survey data from 2008-2022, this study examines the perception of corruption in EU member states. Methods: As a method, the authors use statistical tests. They examine the differences between geographical regions and created country clusters to examine the effect of geographical location on the perception of corruption. They managed to show a difference between north and south. Findings: Based on the results, the role of the cultural and historical background is the most significant in the perception of corruption. Other influences, such as democratization, play a role in shaping opinions. However, the impact of the anti-corruption fight is evaluated independently of the region. It is also a common opinion that corruption cannot be eradicated. Novelty: This study provides a structured approach to analysing corruption perception across regions, emphasizing statistical validation. The findings contribute to understanding the persistence of corruption perception and highlight key influencing factors.